Revitalization of Local Languages Through Educational Curriculum: Strategies and Implications - Subiantoro; Ali, M. Makhrus; Firdaus, Fauzan Akmal (International Journal of Language and Culture, 2023)
The decline in the use of local languages among Indonesia’s younger generations is an urgent issue, where the dominance of Indonesian and foreign languages is increasingly limiting the space for regional languages in daily life. This study aims to identify strategies for revitalizing local languages through the educational curriculum and to examine the challenges encountered in its implementation. The research method used in this study is a literature review, analyzing relevant articles, journals, and policy documents. The findings indicate that although integrating regional languages into the curriculum has been undertaken, significant challenges include teacher training, limited high-quality teaching materials, and insufficient policy support. Therefore, to ensure the revitalization of local languages, collaboration between the government, educational institutions, and the community is needed, along with developing a more adaptive curriculum and supporting resources.